Aberrant expression of CD10 and BCL6 in mantle cell lymphoma. Issue 5 (8th August 2017) - Pizzi, Marco; Agostinelli, Claudio; Righi, Simona; Gazzola, Anna; Mannu, Claudia; Galuppini, Francesca; Fassan, Matteo; Visentin, Andrea; Piazza, Francesco; Semenzato, Gianpietro C; Rugge, Massimo; Sabattini, Elena
Abstract : Aims: Mantle cell lymphoma (MCL) is characterized by distinctive histological and molecular features. Aberrant expression of BCL6 and CD10 has been reported occasionally, but the biological features of such cases are largely unknown. This study aimed to define the epidemiological, histological and cytogenetic characteristics of BCL6 and CD10‐positive MCLs, also investigating possible biological features. Methods and results: A total of 165 cases of cyclin D1 and t(11;14)(q13;q34)‐positive MCLs were studied for CD10 and BCL6 immunohistochemical expression, which was documented in 26 of 165 (15.8%) cases (BCL6 17 of 165; CD10 11 of 165; BCL6 and CD10 co‐expression two of 165). CD10‐positivity was significantly more frequent in females (63.3%; P < 0.01). Either expression correlated significantly with higher mean proliferation index and higher prevalence of MUM1 positivity ( P < 0.05). Fluorescence in‐situ hybridization (FISH) for BCL6 (3q27) gene derangements was performed on the BCL6‐ and CD10‐positive cases and 98 matched controls: amplifications were documented more frequently in BCL6‐positive than ‐negative cases (50.0% versus 19.4% of cases) ( P < 0.05). The mutational status of the variable immunoglobulin heavy chain genes ( IGVH ) was investigated by Sanger sequencing: five of the six successfully tested cases (83.3%) showed no somatic hypermutations. Conclusions: Aberrant CD10 and BCL6 expression defines a subset of MCLs with higher mean Ki‐67 index and higher prevalence of MUM1 expression. BCL6 protein positivity correlates with cytogenetic aberrations involving the BCL6 gene. Although examined successfully in few cases, the high prevalence of unmutated IGVH genes also points at a pregerminal cell origin for these phenotypically aberrant cases.